Accuracy and Performance of Continuous Glucose Monitors in Athletes. Issue 20 (2015) - Thomas, Felicity; Pretty, Christopher G.; Signal, Matthew; Chase, J. Geoffrey
Abstract: Continuous glucose monitoring (CGM) devices, with their 1-5 minute measurement interval, allow blood glucose dynamics to be captured more frequently and less invasively than traditional measures of blood glucose concentration (BG). These devices are primarily designed for the use in type 1 and type 2 diabetic patients to aid BG regulation. However, because of their increased measurement frequency and reduced invasiveness CGM devices have been recently applied to other subject cohorts, such as intensive care patients and neonates. One unexamined cohort is athletes. Continuous monitoring of an athlete's BG has the potential to increase race performance, speed recovery, and aid training, as BG can reflect metabolic and inflammatory conditions. However, before these benefits can be realized the accuracy and performance of CGM devices in active athletes must be evaluated. Two Ipro2 CGM devices (Medtronic Minimed, Northridge, CA, USA) were inserted into an athlete (resting HR 50 beats per minute (bpm), training 10-17hrs per week). Two fasting exercise tests were carried out 3 days apart, involving 2 hours of continuous exercise and a glucose bolus at the end of the 2 hours. Reference BG measurements were taken regularly. These tests were then repeated while the athlete was sedentary, HR < 80bmp. CGM devices agree well with each other and reference measurements during rigorous exercise with a median [IQR] MARD of 7.3 [5.4 - 10.9] %. During sedentary periods the accuracy of the CGM trace compared to reference measurements was reduced, 25.1 [16.9 35.4] %. However the good agreement between the sensors is maintained. This decrease in accuracy is likely related to the fact interstitial fluid is not actively pumped like blood. It relies on muscle movement to circulate and mix. Thus, it can be expected that during exercise more accurate results are seen as the rigorous movement allows rapid mixing and equilibrium between the blood and interstitial fluid.